Analisis Dampak Berganda (Multiplier Effect) Objek Wisata Pantai Watu Dodol Banyuwangi - Adetiya Prananda Putra; Tantri Wijayanti; Jimmi Sandi Prasetyo (Diploma Travel Business, Faculty of Social and Political Science, Jember University, 2019)
Abstract Watu Dodol beach is one of tourism object located in Banyuwangi regency. Banyuwangi government intensively expanding Watu Dodol beach as a tourism icon. Development of tourism industry is directly able to create job opportunity for local community. If it happens, tourism activity in Watu Dodol beach can create multiplier effect that is profitable for local economic and community welfare. Technic analysis used are descriptive analysis to identify all stakeholders and Keynesian income multipliers analysis to identify multiplier effect in Watu Dodol beach. The result of this research showed that general assessment of tourist, entrepreneur, and employee toward beach condition is at medium and high level except on the management aspect. They hope that there will be a special attention from Banyuwangi government to solve that problem. The result also showed that Watu Dodol beach gives real economic impact for local community such as direct impact, undirect impact, and induction impact. Keywords: Keynesian income multiplier, multiplier effect, Watu Dodol beach